Analytic Theology as Sapiential Theology: A Response to Jordan Wessling - Vanhoozer, Kevin J. (Open theology, 2017)
This article responds to Jordan Wessling’s paper that engages a concern I expressed about analytic theology not doing justice to the sapiential requirements of theology. I examine Wessling’s summary of my paper, conclude that his description is accurate and fair, appreciate his proposed solution, then go on to restate why I think he may not have fully allayed my concern. I suggest that analytic theology is a vital tool in the theologian’s toolkit, but that ultimately more is needed in order to interpret Scripture theologically.